Antioxidante enzimático en hipertensos del Distrito del Victor Larco - Alcántara Gutierrez, Yoel Segundo (2018)
In the present work, the level of antioxidants was determined in adults of the district of Victor Larco-Trujillo in the month of February 2018. The sample was taken with all possible ethical and health measures and the superoxide dismutase was analyzed (SOD ), erythrocytic by the method of Minsra and Fridovich, which is based on the inhibition of epinephrine to adenochrome. In addition, data such as weight, height, blood pressure, lifestyles and recent diseases and their treatments were collected. The results obtained were: 14 hypertensive patients diagnosed and 7 with high blood pressure at the time of the investigation. Likewise, 90% of male patients and 92.5% of female patients had concentrations below the normal SOD values, which are 110 - 180 U / ml. Also that the enzyme is decreasing according to age, 34.8% of patients had an age between 66-82 years had low values of SOD. In addition, 100% of patients who had diagnosed arterial hypertension and 96.8% of patients who did not exercise had low values of SOD. It was demonstrated by Pearson's linear correlation that high values of systolic and diastolic blood pressure have low concentrations of SOD. In conclusion, the level of superoxide dismutase is intimately related to the development and maintenance of arterial hypertension and that in turn this enzyme is below the normal values (110-180 U / ml).